2017
DOI: 10.1016/j.envint.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impacts of ambient air pollution in the National Social Health and Aging Project (NSHAP) cohort

Abstract: Background Pathways through which air pollution may impact cognitive function are poorly understood, particularly with regard to whether and how air pollution interacts with social and emotional factors to influence cognitive health. Objective To examine the association between air pollutant exposures and cognitive outcomes among older adults participating in the National Social Life, Health, and Aging Project (NSHAP) cohort study. Methods Measures of cognitive function, social connectedness, and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…Significant variations were also observed at WGUBNL (Amsterdam) and GNUBFR (Paris) (σ = 0.93 µg/m 3 and 1.00 µg/m 3 , respectively), as well as higher PM 2.5 concentrations in autumn and winter. Despite some relevant monthly variations (σ = 1.08 µg/m 3 Strong monthly variations were also observed at the suburban background site of LISBCZ (Prague), urban centre site of SIUCTR (Istanbul) and roadside site of ARRSFR (Paris) (σ = 1.81 µg/m 3 , 2.01 µg/m 3 and 1.57 µg/m 3 , respectively). At these sites, a U-shaped profile was observed during spring and summer, with higher PM 2.5 levels happening during autumn and winter.…”
Section: Analysis Of the Study Periodmentioning
confidence: 96%
See 1 more Smart Citation
“…Significant variations were also observed at WGUBNL (Amsterdam) and GNUBFR (Paris) (σ = 0.93 µg/m 3 and 1.00 µg/m 3 , respectively), as well as higher PM 2.5 concentrations in autumn and winter. Despite some relevant monthly variations (σ = 1.08 µg/m 3 Strong monthly variations were also observed at the suburban background site of LISBCZ (Prague), urban centre site of SIUCTR (Istanbul) and roadside site of ARRSFR (Paris) (σ = 1.81 µg/m 3 , 2.01 µg/m 3 and 1.57 µg/m 3 , respectively). At these sites, a U-shaped profile was observed during spring and summer, with higher PM 2.5 levels happening during autumn and winter.…”
Section: Analysis Of the Study Periodmentioning
confidence: 96%
“…In particular, because of its small size and capacity to penetrate deeply in the human respiratory system, PM 2.5 (PM with an aerodynamic diameter of less than 2.5 µm) is associated with harmful effects on human health, especially on a long-term exposure [2]. Those effects include fatal cardiovascular and respiratory diseases and decreased cognitive functions [3,4]. In addition, it has been linked to environmental concerns, such as visibility impairment (haze) and damage in ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Dementia, delirium, and depression syndromes have a high degree of overlap, can exist simultaneously in the same patient, and often increase the risk for each other 24 . Recent literature has suggested that the impacts of PM2.5 on cognition are mediated by mood disorders such as depression 25 . The possible impact of short-term pollution exposure on mood in surgical patients should also be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Women are thought to have less cognitive functional capacity and experience greater levels of disability or frailty than men 28 . Elevated levels of anxiety may be one reason underlying why women are more susceptible than men to the effects of ambient pollution on delirium 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The adverse health effects of air pollution exposure on human health are well documented (Brunekreef and Holgate 2002, Kampa and Castanas 2008, Apte et al 2015, Oudin et al 2016, Woodward and Levine 2016. Among others, air pollution has negative influence on fetal and infant health (Chay and Greenstone 2003, Currie and Neidell 2005, Luechinger 2014), hinders lung development in children (Gauderman et al 2004) and impacts on cognitive function (Tallon et al 2017, Zhang et al 2018. The effects of air pollution are discernible on human activity (Graff Zivin and Neidell 2013).…”
Section: Introductionmentioning
confidence: 99%